Promotion of Free Shipping and Cash On Delivery (COD) Payments for Purchase Decisions on the Shopee Application for 2019 Stambuk Economic Education Students at HKBP Nommensen University, Pematang Siantar - Melvani Lumbanraja (International Journal of Integrated Science and Technology, 2023)
This research aims to gain knowledge regarding the influence of free shipping promotions and cash on delivery (COD) payments on purchasing decisions on the Shopee application among 2019 Stambuk economic education students at HKBP Nommensen University Pematang Siantar. This type of research is quantitative research with a quantitative descriptive data analysis approach with the testing media used is SPSS 21. The population in this study was 111 people, and the sample used was 70 people. The sample collection technique used was a purposive sampling technique. The data collection technique used was a questionnaire. The hypothesis data collection technique uses multiple regression analysis and the coefficient of determination (R2). The results of this study state that: 1) there is a positive and significant influence of the free shipping promotion on students' purchasing decisions. This result can be seen in the t test where the t value of the free shipping promotion (4.284) > t table value (1.6679) which means the variable is significant. 2) there is a positive influence of cash on delivery (COD) payments on purchasing decisions. This result can be seen in the t test where the t value of cash on delivery (COD) payments (1.915) > t table value (1.6679). 3) free shipping promotions and cash on delivery (COD) payments together influence purchasing decisions. This result can be seen in the F test where the Fcount value (24,640) > Ftable value (2.73). The R Square coefficient of determination test was found to be 0.424%, which means that 21.6% of the free shipping promotion variables and cash on delivery (COD) payments influenced the purchasing decisions of 2019 Stambuk economics education study program students at HKBP Nommesen Pematang Siantar University and 57.3% is the influence of other variables not examined in this research.